The Ndr/LATS Kinase Cbk1 Regulates a Specific Subset of Ace2 Functions and Suppresses the Hypha-to-Yeast Transition in Candida albicans - Rohan S. Wakade (American Society for Microbiology, 2020)
ABSTRACT The regulation of Ace2 and morphogenesis (RAM) pathway is an important regulatory network in the human fungal pathogen Candida albicans. The RAM pathway’s two most well-studied components, the NDR/Lats kinase Cbk1 and its putative substrate, the transcription factor Ace2, have a wide range of phenotypes and functions. It is not clear, however, which of these functions are specifically due to the phosphorylation of Ace2 by Cbk1. To address this question, we first compared the transcriptional profiles of CBK1 and ACE2 deletion mutants. This analysis indicates that, of the large number of genes whose expression is affected by deletion of CBK1 and ACE2, only 5.5% of those genes are concordantly regulated. Our data also suggest that Ace2 directly or indirectly represses a large set of genes during hyphal morphogenesis. Second, we generated strains containing ACE2 alleles with alanine mutations at the Cbk1 phosphorylation sites. Phenotypic and transcriptional analysis of these ace2 mutants indicates that, as in Saccharomyces cerevisiae, Cbk1 regulation is important for daughter cell localization of Ace2 and cell separation during yeast-phase growth. In contrast, Cbk1 phosphorylation of Ace2 plays a minor role in C. albicans yeast-to-hypha transition. We have, however, discovered a new function for the Cbk1-Ace2 axis. Specifically, Cbk1 phosphorylation of Ace2 prevents the hypha-to-yeast transition. To our knowledge, this is one of the first regulators of the C. albicans hypha-to-yeast transition to be described. Finally, we present an integrated model for the role of Cbk1 in the regulation of hyphal morphogenesis in C. albicans. IMPORTANCE The regulation of Ace2 and morphogenesis (RAM) pathway is a key regulatory network that plays a role in many aspects of C. albicans pathobiology. In addition to characterizing the transcriptional effects of this pathway, we discovered that Cbk1 and Ace2, a key RAM pathway regulator-effector pair, mediate a specific set of the overall functions of the RAM pathway. We have also discovered a new function for the Cbk1-Ace2 axis: suppression of the hypha-to-yeast transition. Very few regulators of this transition have been described, and our data indicate that maintenance of hyphal morphogenesis requires suppression of yeast phase growth by Cbk1-regulated Ace2.